Đề xuất mô hình giáo dục nghệ thuật cho học sinh trung học cơ sở tỉnh Nghệ An theo hướng học tập trải nghiệm - Lê, Vũ Anh; Phạm Minh Hùng, Phạm Minh Hùng (Tạp chí Giáo dục, 2026)
Experiential art education for secondary school students is a topical issue with significant theoretical and practical implications. This approach requires the development of effective educational models aligned with the 2018 National Curriculum. Based on clarifying the theory of experiential art education for junior high school students, this paper proposes four art education models for secondary school students in Nghe An province: Music education linked to the heritage of Nghe An; Extracurricular art education in the natural environment of Nghe An; Collaboration with artisans and craft village communities; Interdisciplinary art clubs (Music - Fine Arts) supported by digital technology. The proposed models are grounded in experiential learning theory and adapted to the socio-cultural and geographical characteristics of Nghe An contributing to narrowing the gap in experiential art education modeling at the local level and applicable to other localities with similar contexts.